Общение в сети Интернет. Просто как дважды два: издания для досуга / В. А. Аксак - Аксак Валерий Александрович (ЭКСМО, 2007)
Экземпляры: (20170502) / Инвентарный номер: 33008 / Цена: 60.39 / Сис.шифр: 32.97 / Авт.знак: А 41 / ББК: 32.973.202